Analisis Pelatihan Terhadap Kinerja Guru Berdasarkan Judgment Based Performance dengan Keterikatan Guru Sebagai Variabel Intervening pada MAN Insan Cendekia Jambi - Alif Tegar Jatmiko; Zulfina Adriani; Fitri Widiastuti (Global Leadership Organizational Research in Management, 2025)
This study aims to see the Effect of Training on Teacher Performance with Employee Engagement as an Intervening Variable at MAN Insan Cendekia Jambi. This study uses a quantitative method with data collection techniques by distributing questionnaires to 35 respondents. Hypothesis testing uses Descriptive Analysis Techniques using SmartPLS software as a data processing tool. The results of this study indicate that Training has a significant positive effect on MAN Insan Cendekia Jambi Teacher Performance. Training has a significant positive effect on Employee Engagement. Employee Engagement has a significant positive effect on Teacher Performance. Training has a significant positive effect on Teacher Performance through Employee Engagement as an intervening variable. Suggestions in this study: teacher performance variables to be more skilled in completing each job and must also have ideas that can solve problems in schools. The principal recommends that the training that has been programmed can be carried out properly to all existing teachers and the training carried out is in accordance with the teachers' areas of expertise so that the results of the training are more optimal and the teachers continue to develop and have better competence. Employee Engagement Variables are recommended by schools in providing support to teachers, namely by providing a comfortable and conducive work environment, clear communication, giving appreciation to teachers, and existing policies that are not focused on one party.